Energy storage negative electrode material, negative electrode plate, preparation method of negative electrode plate, battery cell and battery
By using the combination of artificial graphite and mesophase carbon microsphere graphite in the negative electrode material of lithium-ion battery, the particle size and dosage are optimized, and the problem of lithium-ion material is solved at high magnification, achieving the improvement of high energy density and long cycle performance.
Patent Information
- Application Number
- CN202510001653.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-18
AI Technical Summary
The existing lithium-ion battery negative electrode materials are prone to lithium deduction at charge and discharge ratios of 1C and above, resulting in capacity attenuation, unable to support long cycle requirements, and insufficient high-temperature performance and storage performance.
The negative electrode material consisting of artificial graphite and mesophase carbon microsphere graphite is used. By preferring particle size and dosage, graphite is distributed in or wrapped in the gap of carbon microsphere graphite, improving the powder pressure and compaction performance of the material, improving capacity, power, cycling performance and high-temperature performance.
The high compaction, high capacity, excellent power performance, 1C cycle performance and high temperature performance of the negative electrode material are achieved, meeting the needs of high energy density energy storage battery cells, and not excising lithium during long cycles.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrochemical technology, and in particular to energy storage negative electrode materials, negative electrode sheets, methods for preparing negative electrode sheets, battery cells and batteries. Background Art
[0002] In recent years, the demand for lithium-ion battery energy storage has been growing, and with the increasingly high technical requirements for energy storage cells, the energy density and long cycle requirements have increased. As for the negative electrode, the capacity requirement has reached more than 350mAh / g. At present, the mainstream negative electrode uses artificial graphite, but in the process of increasing capacity and compaction, the kinetic properties of graphite are affected. When the charge and discharge rate is 1C or above, it is very easy to precipitate lithium and cause capacity decay, which cannot support the long cycle requirements of energy storage cells. At present, most manufacturers use easily graphitized raw materials, such as needle coke, for low-temperature graphitization control, controlling the capacity at 350, and improving the kinetic properties of needle coke graphite on the basis of ensuring capacity. However, the graphitization process of this method is difficult to control and cannot be supplied stably in large quantities.
[0003] Patent CN118619266A relates to a method for preparing a high-rate graphite negative electrode material, which uses waste graphite electrodes, needle coke, mesophase carbon microspheres, BFBAEPY-COF self-polymerized ligands, and spinning pitch as raw materials; the BFBAEPY-COF self-polymerized ligands are embedded in the needle coke through ball milling and asphalt modification to improve energy storage and rate performance, and improve cyclability; the graphite electrodes, mesophase carbon microspheres, and spinning pitch are briquetting and granulating to improve the structure of the material, achieve good bonding, improve the capacity, rate, and cycle life of the material, give full play to the comprehensive advantages of the material, and take into account the improvement of energy storage capacity, charge and discharge speed, and cycle life. However, this method has a significant adverse effect on high temperature performance and storage performance, and is not suitable for energy storage projects.
[0004] Patent CN111232970B discloses a graphite negative electrode material, lithium-ion battery, preparation method and application: a mixture of mesophase carbon microspheres, anthracite powder and catalyst is graphitized at high temperature; wherein the mass ratio of the mesophase carbon microspheres to the anthracite powder is 1:9-8:1; the particle size D50 of the anthracite powder is 10-20 μm. The graphite negative electrode material prepared by the preparation method of the present invention has a high compaction density, which correspondingly improves the energy density of the battery. However, the invention graphitizes the carbon microspheres and anthracite after mixing, the raw materials are unevenly distributed, it is difficult to evenly transfer heat during the graphitization process, and the graphitization will deteriorate. Summary of the invention
[0005] The first purpose of the invention: The present invention is mainly aimed at projects with 1C room temperature cycle requirements, and develops a graphite negative electrode. On the basis of ensuring the long cycle performance of the material, the rate performance of the material is improved to ensure that there is no lithium precipitation when cycling at 1C, and the 1C room temperature cycle capability of the material is improved; the second purpose of the invention: to provide a negative electrode sheet compacted at 1.6g / cc or above to meet the needs of high energy density and meet high temperature performance; the third purpose is to provide a negative electrode material with a capacity of more than 350mAh / g; the fourth purpose: to provide a battery cell and a battery using the energy storage negative electrode material of the present application.
[0006] In a first aspect, the present application provides an energy storage negative electrode material:
[0007] An energy storage negative electrode material is composed of graphite and mesophase carbon microsphere graphite, wherein the graphite particle size D1 and the mesophase carbon microsphere graphite particle size D2 satisfy 0.1D2≤D1≤D2, and the mass ratio of the graphite to the mesophase carbon microsphere graphite is (0.5-0.95):(0.05-0.5).
[0008] In the present application, the particle size of artificial graphite is small, which can improve the power performance of the material, but if it is too small, it is not conducive to compaction and high-temperature performance; the particle size of carbon microsphere graphite is relatively large, which improves the compaction of the material, but if it is too large, the power becomes worse; the particle size and amount of artificial graphite and carbon microsphere graphite are preferably selected so that the graphite can be better distributed in the gaps of carbon microsphere graphite or the graphite can better wrap the carbon microsphere graphite in the middle, which is beneficial to improve the powder pressure of the material and thus improve the compaction of the negative electrode sheet, thereby improving the capacity, power, 1C cycle performance and high-temperature performance of the negative electrode material, and no lithium precipitation.
[0009] The particle size of the artificial graphite in the negative electrode is smaller than that of the carbon microsphere graphite. The artificial graphite is distributed in the gaps of the carbon microsphere graphite or the artificial graphite wraps the carbon microsphere graphite in the middle. This distribution method is conducive to improving the powder pressure of the material and thus improving the compaction of the negative electrode sheet.
[0010] The particle size of artificial graphite in the negative electrode is small, which can improve the power performance of the material, but if it is too small, it will be detrimental to compaction and high-temperature performance; the particle size of carbon microsphere graphite is large, which improves the compaction of the material, but if it is too large, the power will deteriorate.
[0011] Furthermore, the particle size of the artificial graphite is 2-20 μm, and the particle size of the mesophase carbon microsphere graphite is 8-25 μm.
[0012] Furthermore, the particle size of the artificial graphite is 5-15 μm, and the particle size of the mesophase carbon microsphere graphite is 10-25 μm.
[0013] Furthermore, the graphite particle size D1 and the mesocarbon microsphere graphite particle size D2 satisfy 0.3D2≤D1≤0.9D2.
[0014] Furthermore, the graphite is artificial graphite, and the raw material of artificial graphite includes one or more combinations of petroleum coke, needle coke, and medium-sulfur coke.
[0015] The graphite and mesophase carbon microspheres are both single-particle graphitized products.
[0016] Furthermore, the negative electrode material is compacted at 1.6 g / cc and above; and the capacity of the negative electrode material is maintained above 350 mAh / g.
[0017] Currently, mainstream energy storage graphite generally has a capacity of about 345mAh / g, and when compacted to 1.45-1.55 g / cc, the cycle performance is 6000 cycles; the energy storage negative electrode material in this application can be compacted to more than 1.6 g / cc, and the cycle performance rises to more than the current 8000 cycles, or even 10000 to 12000 cycles.
[0018] In a second aspect, the present application provides a negative electrode sheet:
[0019] A negative electrode sheet comprises a current collector and a film layer formed by the negative electrode material of the present application and attached to the current collector.
[0020] Furthermore, the proportion of negative electrode material in the negative electrode material film layer is 90-98%.
[0021] In a third aspect, the present application provides a method for preparing a negative electrode sheet:
[0022] A method for preparing a negative electrode sheet, comprising mixing the negative electrode material with a water-based or oil-based binder, adding a conductive agent and SBR, and dispersing the negative electrode material and spraying or rolling the negative electrode material film on a current collector to obtain the negative electrode material film layer; the coating is one of single-sided or double-sided; the single-sided surface density of the negative electrode material film layer is 50-120 g / m 2 .
[0023] In a fourth aspect, the present application provides a battery cell, using the negative electrode sheet or negative electrode material described in the present application; the present application provides a battery, using one of the negative electrode sheet, negative electrode material or battery cell described in the present application.
[0024] Beneficial effects:
[0025] 1) In the negative electrode material of the present application, artificial graphite (accounting for more than 50%) and carbon microsphere graphite are preferably used, and the particle size and dosage are further optimized, so that the graphite is better distributed in the gaps of the carbon microsphere graphite or the graphite can better wrap the carbon microsphere graphite in the middle, and the high capacity of the graphite and the high power of the intermediate phase carbon microsphere graphite are effectively matched to prepare a negative electrode material with high compaction, high capacity, excellent power performance, 1C cycle performance and high temperature performance, which meets the market demand for energy storage cells with high energy density.
[0026] 2) The negative electrode material of the present application uses fewer types of materials, so that the high capacity of graphite and the high power of mesophase carbon microsphere graphite are effectively coordinated to prepare a negative electrode material with high compactness, high capacity, excellent power performance, 1C cycle performance and high temperature performance, so that the capacity of the negative electrode material is maintained above 350 mAh / g without lithium precipitation. DETAILED DESCRIPTION
[0027] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below in conjunction with specific embodiments.
[0028] Example 1-1, a negative electrode sheet, the specific steps of preparing the negative electrode sheet are as follows:
[0029] 1) The needle coke artificial graphite with a particle size of 12 microns and the mesophase carbon microsphere graphite with a particle size of 15 microns are mixed evenly in a mixer at a ratio of 90:10 to prepare a negative electrode material.
[0030] 2) Prepare a CMC glue solution with a solid content of 1.4%, stir the negative electrode material and the CMC glue solution in a homogenization tank for 6 hours, add a conductive agent, carbon black is selected as the conductive agent (other conventional conductive agents, such as carbon fiber, can be used in other embodiments of the present invention), stir for 2 hours, add the mixed negative electrode prepared in step 1, stir for 5 hours, adjust the viscosity to 5000-8000 Pa·S with deionized water, add SBR with a solid content of 48%, the above-mentioned addition amount satisfies the negative electrode material: conductive agent: CMC: SBR = 95.5:1:1.5:2, adjust the viscosity to 6000 Pa·S with deionized water, and sieve the material after vacuuming.
[0031] 3) Use an extrusion coater to coat and bake on both sides of a 6μm thick copper foil, and adjust the single-sided density to 75 g / m 2 .
[0032] Use a roller to roll the negative electrode. During the rolling process, adjust the roller gap and pressure until the thickness of the electrode no longer changes or the electrode is wrinkled and bulged. Adjust the pressure and roller gap until the thickness is 100 μm.
[0033] Example 1-2, a negative electrode sheet, is different from Example 1-1 in that in step 1), needle coke artificial graphite with a particle size of 12 microns and mesophase carbon microsphere graphite with a particle size of 15 microns are mixed evenly in a mixer in a ratio of 50:50.
[0034] Embodiment 1-3 is a negative electrode sheet, which is different from Embodiment 1-1 in that in step 1), the needle coke artificial graphite used is needle coke artificial graphite with a particle size of 5 microns.
[0035] Example 1-4 is a negative electrode sheet, which is different from Example 1-1 in that in step 1), the needle coke artificial graphite used is needle coke artificial graphite with a particle size of 15 microns.
[0036] Example 1-5 is a negative electrode sheet, which is different from Example 1-1 in that the mesophase carbon microsphere graphite in step 1) uses mesophase carbon microsphere graphite with a particle size of 25 microns.
[0037] Example 1-6, a negative electrode sheet, differs from Example 1-1 in that in step 1), medium-sulfur coke with a particle size of 12 microns is used to replace the needle coke artificial graphite with a particle size of 12 microns in an equal amount.
[0038] Comparative Example 1-1 is a negative electrode sheet, which differs from Example 1-1 in that in step 1), an equal amount of 12 μm needle coke artificial graphite is used to replace the negative electrode material.
[0039] Comparative Example 1-2 is a negative electrode sheet, which is different from Example 1-1 in that in step 1), an equal amount of 15 μm mesophase carbon microsphere graphite is used to replace the negative electrode material.
[0040] Comparative Example 1-3 is a negative electrode sheet, which is different from Example 1-1 in that in step 1), needle coke graphite with a particle size of 15 microns and mesophase carbon microsphere graphite with a particle size of 12 microns are used.
[0041] Comparative Example 1-4 is a negative electrode sheet, which is different from Example 1-1 in that in step 1), needle coke graphite with a particle size of 2 microns and mesophase carbon microsphere graphite with a particle size of 25 microns are used.
[0042] Performance test of negative electrode:
[0043] 1) Extreme compaction of negative electrode sheets: The negative electrode sheets of Examples 1-1 to 1-6 and Comparative Examples 1-1 to 1-4 were rolled in sequence, and the roller gap and pressure were adjusted until the thickness of the electrode sheets no longer changed or the electrode sheets were wrinkled and bulged, and the extreme compaction of the negative electrode sheets was tested.
[0044] 2) The negative electrode sheets (compacted 1.6 g / cc) of Examples 1-1 to 1-6 and Comparative Examples 1-1 to 1-4 were used in sequence as working electrodes, metallic lithium was used as counter electrode, celgard 2400 was used as separator, the electrolyte contained LiPF6, DMC, DEC and EC, the concentration of LiPF6 in the electrolyte was 1 mol / L, DMC:DEC:EC (wt%)=1:1:1, and button batteries were prepared; then the button batteries were subjected to charge and discharge tests, and the measured capacity and initial efficiency of the materials in the electrode sheets are shown in Table 1:
[0045] Table 1. Test results of limit compaction, capacity and first efficiency of negative electrode sheets of Examples 1-1 to 1-6 and Comparative Examples 1-1 to 1-4
[0046] distinguish Ultimate compaction g / cc Capacity mAh / g First effect Example 1-1 1.72 354.5 94.30% Example 1-2 1.73 351.2 94.50% Examples 1-3 1.6 (ear wrinkles) 352.5 93.50% Examples 1-4 1.66 353.1 94.10% Examples 1-5 1.78 353.8 94.55% Examples 1-6 1.68 353.6 92.80% Comparative Example 1-1 1.65 355.7 94.65% Comparative Example 1-2 1.61 346.1 93.20% Comparative Examples 1-3 1.73 354.2 94.10% Comparative Examples 1-4 1.51 348.7 92.40%
[0047] Embodiment 2-1, a battery cell, the preparation process of which includes the following preparation steps:
[0048] The negative electrode sheet of Example 1-1 was used as the working electrode, and iron lithium was used as the positive electrode to prepare a 5Ah soft-pack battery cell by Z-shaped lamination.
[0049] Embodiment 2-2 to embodiment 2-6 are a kind of battery cell, which is different from embodiment 2-1 in that the negative electrode sheets are the negative electrode sheets of embodiment 1-2 to embodiment 1-6 in sequence.
[0050] Comparative Examples 2-1 to Comparative Examples 2-3 are a type of battery cell, which differs from Example 2-1 in that the negative electrode sheets are the negative electrode sheets of Comparative Examples 1-1 to Comparative Examples 1-3, respectively.
[0051] Performance testing:
[0052] The battery cells of Example 2-1 and Example 2-6 and the battery cells of Comparative Examples 2-1 to 2-3 were subjected to charge and discharge tests. The test items included DCR (DC internal resistance), 1C room temperature cycle, 1C high temperature cycle, and capacity retention rate after 2000 cycles of cycle test. The test results are shown in Table 2 below:
[0053] Table 2. Test results of DCR, normal temperature cycle capacity retention rate and high temperature cycle capacity retention rate of the battery cells of Examples 2-1 to 2-6 and Comparative Examples 2-1 to 2-3
[0054] distinguish DCR / mΩ Normal temperature (25°C) 1C cycle capacity retention rate High temperature (45°C) 1C cycle capacity retention rate Example 2-1 10.8 93.40% 85.70% Example 2-2 9.8 93.80% 84.10% Example 2-3 8.9 92.50% 83.80% Embodiment 2-4 12.1 91.60% 86.30% Embodiment 2-5 13.2 90.30% 86.40% Embodiment 2-6 10.4 93.70% 85.20% Comparative Example 2-1 11.7 91.90% 85.20% Comparative Example 2-2 10.1 93.20% 82.50% Comparative Examples 2-3 12.9 90.90% 87.60%
[0055] After the disassembly experiment was completed after 2000 cycles, the battery cells were disassembled to confirm that: Examples 1 to 1-6 did not deposit lithium during the 1C cycle at room temperature, Comparative Examples 2-1 and 2-3 deposited lithium slightly, and Comparative Example 2-2 did not deposit lithium.
[0056] As can be seen from Examples 1 and 2 in Table 1, increasing the amount of needle coke graphite can improve the capacity, compaction, and high-temperature performance of the negative electrode. There is no lithium precipitation at room temperature at 1C. Moreover, only when the proportion of needle coke is larger can the negative electrode capacity be maintained above 350 mAh / g. However, the power and room-temperature 1C cycle performance of the negative electrode will deteriorate. As can be seen from Examples 1, 3, and 4, the particle size of needle coke graphite has a greater impact on the compaction and rate performance of the negative electrode. When the particle size of needle coke is too small, the compaction of the negative electrode is low and cannot meet the requirements. When the particle size of needle coke is too large, the power of the negative electrode is poor, resulting in poor room-temperature 1C cycling. As can be seen from Examples 1 and 5, increasing the particle size of carbon microsphere graphite deteriorates the power of the negative electrode and the room-temperature 1C cycle. As can be seen from Examples 1, 4, and Comparative Example 3, only when the particle size of needle coke graphite with a larger proportion ≤ the particle size of carbon microspheres can higher power performance and room-temperature cycle performance be obtained. From the above results, it can be seen that the appropriate particle size range is 0.1D2 ≤ D1 ≤ D2. When 0.1D2 < D1 (Comparative Example 4), the slurry dispersion is difficult, the compaction of the electrode sheet is low, and the usage requirement of 1.6 cannot be met. In addition, due to the too small particle size, the capacity of needle coke cannot be too high, resulting in the final negative electrode capacity not reaching above 350. When D1 > D2 (Comparative Example 3), the particle size of needle coke is too large and the power is too high, resulting in poor room-temperature cycling. The preferred particle size range is D1 > 5, D2 ≤ 25. When D1 is too small (Example 3), the ultimate compaction of the negative electrode sheet is 1.6, and at this time, the tab is wrinkled, which has an adverse effect on long-term cycling. When D2 > 25 (Example 5), the overall power of the negative electrode deteriorates, resulting in poor room-temperature cycle performance. The preferred particle size range is 0.3D2 ≤ D1 ≤ 0.9D2. When the particle size difference between needle coke and carbon microspheres is too large, the particle size of the needle coke component with a larger proportion will be very small. At this time, the processing of the negative electrode slurry is relatively not so easy. In Example 3, even though it meets the range of 0.3D2 ≤ D1 ≤ 0.9D2, due to the needle coke particle size being about 5 microns, the slurry is still difficult to disperse and the material compaction is also very difficult.
[0057] The above-described embodiments merely represent several implementation manners of the present invention. The description is relatively specific and detailed, but it should not be construed as a limitation on the scope of the invention patent of the present invention. It should be noted that for those of ordinary skill in the art, without departing from the concept of the present invention, several modifications and improvements can still be made, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the invention patent of the present invention should be subject to the appended claims.
Claims
1. An energy storage negative electrode material, characterized in that: The invention is composed of graphite and mesophase carbon microsphere graphite, wherein the graphite particle size D1 and the mesophase carbon microsphere graphite particle size D2 satisfy 0.1D2≤D1≤D2, and the mass ratio of the graphite to the mesophase carbon microsphere graphite is (0.5-0.95):(0.05-0.5).
2. The energy storage negative electrode material according to claim 1, characterized in that: The particle size of the artificial graphite is 2-20 μm, and the particle size of the mesophase carbon microsphere graphite is 8-25 μm.
3. The energy storage negative electrode material according to claim 2, characterized in that: The particle size of the artificial graphite is 5-15 μm, and the particle size of the mesophase carbon microsphere graphite is 10-25 μm.
4. The energy storage negative electrode material according to claim 2, characterized in that: The graphite particle size D1 and the mesophase carbon microsphere graphite particle size D2 satisfy 0.3D2≤D1≤0.9D2.
5. The energy storage negative electrode material according to claim 1, characterized in that: The graphite is artificial graphite, and the raw material of artificial graphite includes one or more combinations of petroleum coke, needle coke, and medium-sulfur coke.
6. The energy storage negative electrode material according to claim 1, characterized in that: The negative electrode material is compacted at 1.6 g / cc and above; and the capacity of the negative electrode material is maintained at above 350 mAh / g.
7. A negative electrode sheet using the energy storage negative electrode material according to any one of claims 1 to 6, characterized in that: It includes a current collector and a negative electrode material film layer attached to the current collector.
8. A method for preparing a negative electrode sheet using the energy storage negative electrode material according to claim 7, characterized in that: The negative electrode material is mixed with a water-based or oil-based binder, and then a conductive agent and SBR are added. After dispersion, the negative electrode material is sprayed or rolled on the current collector to obtain a negative electrode material film layer; the coating is one of single-sided or double-sided; the single-sided surface density of the negative electrode material film layer is 50-120 g / m 2 .
9. A battery cell, characterized in that: The negative electrode material or negative electrode sheet according to any one of claims 1 to 7 is used.
10. A battery, characterized in that: Adopt one of the negative electrode materials, negative electrode sheets and battery cells described in any one of claims 1 to 7 and 9.
Citation Information
Patent Citations
A graphite anode material, a lithium-ion battery, a preparation method, and applications.
CN111232970B